The influence of temperature in the production of intermediate compounds of acid degradation of D-glucose - Руденко, В. М. (Problems of Environmental Biotechnology, 2019)
In the paper there is considered the question of the influence of temperature on the course of the early stages of degradation D-glucose in aqueous solutions in pH range 1,0–7,0. By Raman spectroscopy there is demonstrated that within the temperature limits of 20–95 °C a change in the concentration of intermediate carbonyl-containing compounds (V 1740–1710 cm-1) is observed, which suggests a certain sequence of transformations of the early stages of degradation D-glucose. By UV-spectroscopy there is demonstrated that the formation of intermediates of the early stages of degradation D-glucose [unsaturated carbonyl-containing compounds, including unsaturated ozone (Lambda(max) 225 nm) and carbonyl-containing compounds (Lambda(max) 285 nm )] increases rapidly within the temperature limits of 80–95 °C in pH range 1,0–7,0. It has been shown that, all processes of the early stages of acid degradation D-glucose are slowed down at pH 3.0 within the limits of given temperatures.